Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

If [tex]\( f(x) = 4 - x^2 \)[/tex] and [tex]\( g(x) = 6x \)[/tex], which expression is equivalent to [tex]\( (g - f)(3) \)[/tex]?

Sagot :

Sure, let's break down the solution step by step for finding [tex]\((g - f)(3)\)[/tex].

First, we are given the functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
[tex]\[ f(x) = 4 - x^2 \][/tex]
[tex]\[ g(x) = 6x \][/tex]

We are required to find [tex]\( (g - f)(3) \)[/tex], which means we need to evaluate both [tex]\( g(3) \)[/tex] and [tex]\( f(3) \)[/tex], and then subtract [tex]\( f(3) \)[/tex] from [tex]\( g(3) \)[/tex].

1. Evaluate [tex]\( f(3) \)[/tex]:
[tex]\[ f(x) = 4 - x^2 \][/tex]
[tex]\[ f(3) = 4 - 3^2 \][/tex]
[tex]\[ 3^2 = 9 \][/tex]
[tex]\[ f(3) = 4 - 9 \][/tex]
[tex]\[ f(3) = -5 \][/tex]

2. Evaluate [tex]\( g(3) \)[/tex]:
[tex]\[ g(x) = 6x \][/tex]
[tex]\[ g(3) = 6 \cdot 3 \][/tex]
[tex]\[ g(3) = 18 \][/tex]

3. Compute [tex]\( (g - f)(3) \)[/tex]:
[tex]\[ (g - f)(3) = g(3) - f(3) \][/tex]
[tex]\[ (g - f)(3) = 18 - (-5) \][/tex]
[tex]\[ (g - f)(3) = 18 + 5 \][/tex]
[tex]\[ (g - f)(3) = 23 \][/tex]

Thus, the expression that is equivalent to [tex]\((g - f)(3)\)[/tex] evaluates to 23.